Digitalisasi Sistem Administrasi Pemerintahan Kota Padang: Analisis Literatur Sistematis - Jumiati, Jumiati; Putri, Amelia Dwi; HRP, Nisa Istiqomah; Marjuwita, Vira; Rahmi, Windy Aulianisa; Hamiathul, Zikra; Saputra, Boni (CV. ITTC INDONESIA, 2025)
This study evaluates the readiness of Padang City’s state administration for the digital era by assessing policy frameworks, infrastructure, human resources, and public perceptions. Using a literature review methodology, it analyzes 47 journal articles from Google Scholar, Google, and ProQuest, published between 2019 and 2025. Inclusion criteria focused on Indonesian and English publications addressing digital government implementation or public administration transformation with technological, organizational, or managerial relevance. Thematic analysis identified patterns, contradictions, and gaps. Findings show that Padang City is in a transitional phase with fragmented and inconsistent digital development. Digital capabilities among government institutions vary, with digitalization scores ranging from 3.2 to 8.7 out of 10. Resistance to change is high, especially among civil servants over 50 years old (68%). IT infrastructure is inadequate, with only 50 Mbps bandwidth (below the 100 Mbps standard), low cybersecurity (4.2/10), and poor interoperability (2.8/10). The average digital competency of 1,247 civil servants is 4.8/10, below the ASEAN average of 7.2/10. Public adoption of digital services is uneven, with 78% usage in online licensing and only 34% in digital health services. The study concludes that comprehensive transformation is needed, including proportional IT budgeting, capacity building, infrastructure improvement, integrated data management, and strengthened leadership.